Forecast-based Monetary Policy in Sweden 1992-1998: A View from Within - Per Jansson; Anders Vredin (Sveriges Riksbank, 2001)
The use of explicit inflation targets has meant that monetary policy has become more transparent and also easier to evaluate. The analysis in this paper is based on forecasts by Sveriges Riksbank (the central bank of Sweden) on real output and inflation. Our purpose is to separate the effects on the interest-rate instrument from (i) discretionary changes in the rule for monetary policy, and (ii) judgements in forecasting. We first feed the Riksbanks forecasts into two different simple rules for interest-rate policy. The differences between the interest rates implied by these benchmark rules and the actual policy rate are interpreted as measures of policy shocks. Second, we compare the Riksbanks forecasts with alternative forecasts. Using a benchmark rule for the setting of the policy rate, we can use the differences between the forecasts to define measures of the effects of the Riksbanks judgements on its interest-rate policy.
Keywords: E37; E42; E52; 330; Central bank forecasts; Inflation targeting; Judgmental forecasts; Monetary policy; Policy rules